Status of birth preparedness and complication readiness in a rural community: a study from West Bengal, India - Rupsa Mazumdar; Dipta K. Mukhopadhyay; Seshadri Kole; Debabrata Mallik; Apurba Sinhababu (Al Ameen Medical College, 2014)
Problems: Birth-preparedness and complication-readiness (BP/CR) is a tool to promote maternal and neonatal survival. This study was conducted to assess the perception and practices of recently delivered women on BP/CR with its correlates. Methods: In a cross-sectional, community-based study, 240 women who delivered in last 12 months, selected through two-stage 30-cluster sampling from a rural community in Bankura district, West Bengal, India were interviewed. Result: Overall BP/CR index of the study population was 49.4. Proportion of women who received first antenatal check-up within first trimester, four or more antenatal check-ups, saved money for childbirth and had institutional delivery were 83.8%, 87.9%, 84.6% and 90.0% respectively. Around one-sixth women had knowledge of key danger signs of obstetric complications and 12.9% identified blood donor. Working women and women of high-risk age group, Muslim religion, and lower educational status had lower BPCR index. Women with multiparity were less likely to have first check-up within 12 weeks, four antenatal check-ups and institutional delivery. Conclusion: Contacts with health system during service utilization can be used to promote BP/CR practices.